The Lifespan Hormesis Phenomenon in a Population does not Make It's Healthier - Shoutko, Aleksey N.; Ekimova, Ludmila P. (Challenges in Disease and Health Research Vol. 5, 2021)
Recently, radiation hormesis has been considered a form of useful cancer therapy when total-body irradiation (TBI) is delivered to a cumulative dose of 1.5 Gy at about 0.1 Gy/day. Many studies have attributed hormesis to potentiation of the immune system. The goal of this study was to evaluate the influence of natural variation in the regenerative status of dog tissues on the signs of hormesis, which are evident after total body exposure to low daily doses of external gamma radiation throughout the lifespan. Ninety beagle dogs of both sexes were irradiated with cobalt 60 at 0.003 Gy/day commencing 1 year after birth to death. Control (n = 169) and irradiated animals underwent whole-life clinical observation and autopsy, and were then retrospectively divided into two subgroups with (W) or without benign tumors or tumors of unknown nature (WO) that were clinically recorded on single days throughout the lifespan. Radiation hormesis was only detected in subgroup WO, which had life span (LS) of 10.7 years in the absence of radiation. The radiogenic prolongation of life to 11.8 years in the WO subgroup (p < 0.05) was similar to that in the W control and irradiated W subgroups (11.8 and 11.5 years, respectively). The number of solid malignancies found upon autopsy of the control WO subgroup was less (39.5%) than that evident in the control W subgroup (60%). Compared to the irradiated W subgroup, irradiation of the WO subgroup was accompanied by a slight increase (1.14-fold) in the number of solid malignancies evident at autopsy and in the clinical signs of tissue atrophy and body weight loss (2.4-fold and 2.4-fold, respectively), but was accompanied by strong reductions in the extent of anemia and hematoblastoses (>10-fold for both). The data exclude the notion that radiation is associated with healing, but suggest that certain pathologies (e.g., hematoblastoses) may be substituted with other less dangerous somatic diseases in weaker animals only. It suggests that the notion of radiobiological “stimulation” is inappropriate, at least in mammals.